Health Policies: Bolstering Human Resources & Healthcare Systems to Reduce Crude Death Rates in 2⁶ Countries - Mohamed Sesay; Rudi Purwono; Ni Made Sukartini (Universitas Udayana, 2025)
This study examines the key determinants of crude death rates (CDR) in selected Countries within Africa, Asia, Europe, and Latin America, emphasising statistical correlations, policy implications, and regional disparities. Using econometric analysis, the study finds that increased life expectancy, higher government healthcare expenditure, and GDP per capita growth significantly reduce mortality rates. Labour force participation and access to potable water further influence mortality trends. However, African and some Asian nations experience higher CDRs due to weak healthcare infrastructure and economic constraints. The findings underscore the need for sustained investment in healthcare systems, human capital development, and policy-driven interventions to mitigate mortality risks and improve public health. This study provides empirical evidence to guide policymakers in designing targeted health policies that enhance healthcare equity and long-term health outcomes.